FEED LYSIN. MEANING AND SYNTHESIS - O. Kananykhina; T. Turpurova; A. Soloviova (Zernovì Produkti ì Kombìkorma)
The intensification of animal husbandry depends on the full feeding of farm animals, which provides for the content of the most important nutrients and biologically active substances in the feed. In order to obtain the necessary amount of high-quality livestock products, to ensure high reproductive capacity of animals, specialists develop animal feeding rations taking into account minimum feed costs. Providing farm animals with fodder protein is one of the important tasks of agriculture and enterprises that produce protein fodder or obtain it in the form of by-products. The use of by-products of food processing is of great importance in animal feeding programs and also solves the problem of disposal of these by-products. The application of such solutions will allow to reduce the need of farms for fodder grain, fodder of animal origin and other expensive components used in feeding. Protein feeds of plant origin include sunflower processing products as the cheapest source of feed protein in Ukraine. The inferiority of the proteins of sunflower cake and meal should be compensated with synthetic amino acids. Lysine, as an essential amino acid, has a wide range of applications, covering various fields from medicine to the food industry and agricultural activities, in particular in the feed industry. Most of the produced lysine is used in the production of feed additives (for pigs and poultry), which significantly increase the nutritional value of vegetable feed with a low lysine content. The addition of lysine to compound feed improves protein digestibility by animals and reduces feed costs for the production of livestock products. Given the availability of lysine and taking into account livestock statistics, namely the increase in the number of pigs and the decrease in the number of cattle and poultry, industrial production of lysine as a feed additive for pigs is a promising direction. The main methods of lysine production are considered - chemical, chemical-enzymatic, biological and microbiological. The technology of each method is analyzed in detail, the advantages and disadvantages of different methods of obtaining lysine are given.